Are European Equity Style Indexes Mean Reverting? Testing the Validity of the Efficient Market Hypothesis - Marian Berneburg (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2004)
The article tests for a random walk in European equity style indexes. After briefly introducing the efficient market hypothesis, equity styles in general and the used statistical techniques (Variance Ratio Test and modified Rescaled Range Test) it is shown that a random walk in European equity style indexes cannot be rejected. At least in the period since the mid 70s, for which this research has been conducted, the weak form efficient market hypothesis seems to hold.
urn:nbn:de:gbv:3:2-5101
Keywords: G11; G14; 330; Efficient Market Hypothesis; Variance Ratio Test; Rescaled Range Test; Equity Style Investment; Börsenkurs; Aktienindex; Random Walk; Mean Reversion; Effizienzmarktthese; Schätzung; Westeuropa